Long-term stable lung function and second uncomplicated pregnancy on sirolimus in lymphangioleiomyomatosis (LAM) - Faehling, Martin; Wienhausen-Wilke, Vera; Fallscheer, Sabine; Trinajstic-Schulz, B.; Weber, J.; Leschke, Matthias (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Dear Sir,we recently reported the case of a successful pregnancy in a patient with lymphangioleiomyomatosis (LAM) (1). In the following, we report the second pregnancy in this patient and the further outcome on sirolimus. In accordance with results of the MILES trial (2), which had demonstrated efficacy of sirolimus in stabilizing lung function of LAM, and due to evolving evidence in favour of long-term therapy with sirolimus (3), the patient was continued on sirolimus adjusted to maintain blood levels of 5-15 µg/l.Three years and ten months after delivery of the first child, the patient, now 34 years old, reported the second pregnancy, then 7th week. The pregnancy had occurred whilst on sirolimus 3 mg o.d. for LAM (trough level 7.3 µg/l). Due to deterioration of lung function after discontinuation of sirolimus during the previous pregnancy, it was decided to continue the therapy of sirolimus, but at a reduced dose of 2 mg o.d., resulting in blood levels of 3.5 µg/l. To prevent a further decline of blood levels, sirolimus was increased back to 3 mg o.d. during the second trimester. This maintained blood levels of around 3.5 µg/l (table 1). After pregnancy, sirolimus levels increased to around 6.5 µg/l without dose adjustment. This points to a faster metabolism of sirolimus during pregnancy in this patient.In contrast to the first pregnancy (off sirolimus from 11th to 21st week) with a sharp decline in lung function, during the second pregnancy (on sirolimus low dose) lung function remained stable. Also in contrast to the first pregnancy, no complications, in particularly no pneumothorax, occurred. The fetus developed normally. At 32 week + 4, a healthy, normally sized female newborn was delivered by Caesarian section. Since then, the child, now 7 months old, has shown a normal development. Having been on continued sirolimus for seven years (with exception of 10 weeks off sirolimus during the first pregnancy), the mother is well and shows stable lung function (table 1).In conclusion, the second pregnancy on uninterrupted sirolimus was uncomplicated both with respect to mother and child suggesting that sirolimus at the dose used may be safe in pregnant patients with LAM. During pregnancy, blood levels of sirolimus declined spontaneously indicating a faster metabolism of the drug. However, even at sirolimus levels considered subtherapeutic in the MILES trial, lung function was preserved during pregnancy in this patient. Since the vast majority of LAM patients are young women with a much improved outcome on sirolimus, a significant number may wish to become pregnant. However, in LAM trials, in particular in the MILES trial, pregnant women are excluded. Therefore, it is important to systematically collect information on the outcome of LAM during pregnancy.